Lymphocyte subset counts as diagnostic and prognostic markers for carbapenem-resistant Enterobacteriaceae (CRE) infection in critically ill patients. (July 2020) - Cheng, Wei; Wang, Hao; Zhang, Jiahui; Bai, Guangxu; Han, Wen; Chen, Jianwei; Cui, Na
Highlights: The 28-day mortality was significantly higher in CRE than non-CRE patients. The T lymphocyte count and CD4 + CD28 + T cell count were both independent risk factors for CRE infection, with the latter having the best diagnostic ability (AUC: 0.908; p < 0.0001). The CRE incidence of sepsis patients and 28-day mortality of CRE-infected patients could be predicted using CD4 + CD28 + T cell count cutoff values of 242 (sensitivity: 83.9%; specificity: 87.5%) and 58.5 (sensitivity: 100%; specificity: 61.1%) cells/μl at ICU admission, respectively. Abstract: Objectives: This study investigated the use of lymphocyte subset counts as diagnostic and prognostic markers for carbapenem-resistant Enterobacteriaceae (CRE) infection. Methods: We assessed the lymphocyte subset populations and other clinical parameters of septic patients upon intensive care unit (ICU) admission, and evaluated their potential impact on CRE infection diagnosis and outcome. Results: Among 373 septic patients, 51 were diagnosed with CRE infection. The 28-day mortality was significantly higher in CRE than non-CRE patients (35.3% vs 14.9%). The T lymphocyte count and CD4 + CD28 + T cell count were both independent risk factors for CRE infection, with the latter had the best diagnostic ability (AUC: 0.908; p < 0.0001). Lower CD4 + CD28 + T cell counts were associated with higher likelihoods of CRE infection. The CRE incidence and 28-day mortality of CRE-infected patients could be predicted using cutoff values of 242 (sensitivity: 83.9%; specificity: 87.5%) and 58.5 (sensitivity: 100%; specificity: 61.1%) CD4 + CD28 + T cells/μl at ICU admission, respectively. Conclusions: Septic patients with CRE infection had higher 28-day mortality. Given that the CD4 + CD28 + T cell count was significantly lower in CRE than non-CRE septic patients and a lower cell count was significantly associated with higher 28-day mortality, CD4 + CD28 + T cell counts may be useful markers for early diagnosis of CRE infection and outcome prediction.